An Assessment of Social Practices of Benmark Holding Incorporation in Relations to Company Growth: Basis for a Proposed Development Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Benmark Holding Incorporation is a food and non-establishment company located on the 20thfloor of Skysuites Tower Quezon Ave., Quezon City. The company is currently havingdifficulties in having social responsibilities for its employees. The researchers recommend aproposed development plan for the company to enhance employees' social responsibilities.Being socially responsible includes having corporate ethics rules that enhance anorganization's social, economic, and environmental performance. By exercising socialresponsibility, businesses can control their impact on society and the actions that are helpfulto society. Through a range of environmental and social efforts, the socially responsiblebusiness demonstrates its commitment to having a beneficial impact on society andcommunities. To benefit employees and society and promote the use of sustainable businesspractices in economics, a corporation should take social responsibility. Being sociallyconscious can give a business a competitive advantage.Based on the assessment of economics, the married respondents strongly agree with 4.4, andsingle respondents very strongly agree with 4.5, which talks about how increasing employeeperformance might increase trust. The married respondents strongly agree with 4.4, andsingle respondents very strongly agree with 4.5 in the assessment of social maintainingrelationships built by every employee. Lastly, in the assessment of the environment, themarried respondents very strongly agree with 4.5, and single respondents strongly agree with4.4, which is the effect of the condition of the workplace on the work efficiency and loyalty ofemployees in a company.The researcher makes conclusions and recommendations for improving the social practiceswithin a company. According to the research findings, the company has ineffective trainingmethods, performance problems, lack of direction in their roles, conflict management, andlack of opportunity for growth, which are the most common problems that employeesencounter. The researchers proposed a development plan for the employees of BenmarkHolding Incorporation. The following are suggested: enhance their social interaction, conductregular team building, social activity, and seminars, recognize the hard work of employees,and employees should do more often in a field to know more about their goals.
Keywords: Business